Neuro-tracing approach to study kidney innervation: a technical note - Lee, Sanghee (Kidney Res Clin Pract, 2017)
Neuro-tracing approach is a great option to study innervation of the visceral organs including the kidneys. Important factors contributing to the success of this technique include the choice of a neuro-tracer, and delivery methods to result in successful labeling of peripheral sensory and motor ganglia. The neuro-tracer is usually applied directly to the kidney accessed via a surgical opening of the abdominal wall under deep anesthesia. A series of local microinjections of the dye are performed followed by a wound closure, and recovery period from the surgery. An extra care should be taken to prevent neuro-tracer spillage and accidental labeling of the surrounding organs during injections of the dye. Retrograde neuro-tracers like Fast Blue do not cross synapses, therefore, only neuronal bodies located within dorsal root ganglion neurons and major peripheral ganglia will be labeled by this approach. Retrogradely labeled peripheral neurons could be freshly isolated and dissociated for electrophysiological recordings and biochemical analyses (gene and protein expression), whereas the whole fixed ganglia could be sectioned to undergo immunohisto- and immunocytochemical targeted staining.